Customer Engagement, Customer Equity, and Their Influence on Consumer Repurchase Intention in E-Commerce Mobile Applications - Dwiviolita, Selsy; Zuliarni, Sri (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2023)
The focus of this research is to determine the effect of customer engagement on repurchase intention using the customer equity dimension mediating the mobile e-commerce application at Shopee Indonesia company. Customer equity has three dimensions: value equity, brand equity, and relationship equity. The research approach is quantitative, with a purposive sampling technique, and the research sample is 160 respondents. This study identified modeling with Structural Equations Analysis (SEM) with SmartPLS 3.29. The findings of this study are that the variable customer engagement has a positive and significant effect on the dimensions of customer equity (value equity, brand equity, and relationship equity). Dimensions of customer equity (value equity, brand equity, and relationship equity) positively and significantly affect repurchase intention. Customer engagement has an indirect and significant positive effect on repurchase intentions mediated by customer equity dimensions (value equity, brand equity, and relationship equity).